KOMPETENSI AWAL PESERTA DIKLAT PADA DIKLAT TEKNIS SUBSTANTIF PENINGKATAN KOMPETENSI MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA BAGI GURU MADRASAH DI KANMENAG KABUPATEN PANGANDARAN TAHUN 2018 - Urip Muryanto (Tatar Pasundan: Jurnal Diklat Keagamaan, 2018)
This study aims to describe the initial competency of the training participants in the Substantive Technical Training on Competency Enhancement of Multimedia-Based Learning Media in the Ministry of Religion of Pangandaran District in 2018 totaling 30 people. The study used descriptive method with a research instrument in the form of a closed questionnaire to all training participants and simple data processing in percentage form. The results showed that the initial competency of participants in the word processing program was 28.89%, internet for learning 33.33%, basic concepts of hardware and software 34.67%, number processing program 35.56% and word processing program 47.78%, so that the average of all aspects of the program is at 35.78%.  Key words: Initial Competency, training, Information and Communication technology, multimedia.